Zoroastrianism. - Rose, Jenny (Guides for the perplexed., 2011)
The history of the development of Zoroastrianism spans over 3000 years, beginning in prehistory as an oral tradition, with roots in a common Indo-Iranian mythology. It then became established as part of an imperial Iranian ideology within an Ancient Near Eastern setting, and eventually emerged in variant forms in Iran, Central Asia and India in late antiquity. Zoroastrianism continues as a living faith for an estimated 150,000 adherents in the world today. Most Zoroastrians, if asked the question, 'In a nutshell, what do Zoroastrians believe?' would begin their answer with 'Good Thoughts, Good.